Les sociétés humaines face aux changements climatiques. - Djindjian, François (Union Internationale des Sciences Préhistoriques et Protohistoriques., 2022)
Is climate change a factor of change for human societies that can be witnessed through time, forcing them to adapt and find sustainable solutions? This book is the first of two volumes exploring human societies facing climate change in pre and protohistory. Volume 1 concerns prehistory from the earliest humans to the end of the Pleistocene.